Pengaruh Disiplin Belajar Terhadap Kemandirian Siswa - Ulfiani Umi Khayati; Nurlinda Safitri; Santa Santa (STKIP Andi Matappa Pangkep, 2023)
This research is a quantitative research through a causality approach, this study aims to determine the effect of learning discipline on student independence. This study was conducted to test the validity of the instrument variables of learning discipline and student independence using the Pearson Product Moment formula and the reliability test using the Alpha Cronbach formula. The population in this study were students in grades IV-A, IV-B, and IV-C IV at SDN Ciantra 01, Cikarang Selatan District, Bekasi Regency, for the 2021/2022 academic year, with a total of 144 students. The sample used was 60 students, which were obtained using the Taro Yamane formula. Furthermore, research data collection was carried out and carried out analysis tests using the Normality, Homogeneity, and Linearity Tests. The results of this study indicate that it can be shown from the regression equation Å¶= 53.82 + (0.54X). This means that the increase or decrease in Student Learning Independence is influenced by the level of Learning Discipline of 0.760 which indicates that the variable of learning discipline has a positive effect on student learning independence by 76%, while the remaining 24% is influenced by other factors.